BowTie analysis of rooftop grid‐connected photovoltaic systems. (19th January 2022) - Mohd Nizam Ong, Nur Aliah Fatin; Mohd Tohir, Mohd Zahirasri; Mutlak, Mays Mahmood; Sadiq, Muhammad Adnan; Omar, Rozita; Md Said, Mohamad Syazarudin
Abstract: With the rapid growth of the worldwide photovoltaic (PV) installation, the number of fire incidents involving PV systems also shows an increasing trend. Several studies revealed that installing PV systems on the rooftop has introduced an additional fire risk to the building. Therefore, risk assessment is required to identify the possible cause of fire initiation involving PV systems and subsequently provide the solar industry with fire risk information regarding PV faults. A BowTie analysis of rooftop grid‐connected PV systems was conducted, where initiation of ignition was determined as the hazard and PV fires as the loss event. Four threats in the BowTie analysis were identified using fault tree analysis, that is, arc fault, ground fault, hotspot effect at PV modules, and overheating. Arc fault contributes the most to PV fire incidents, while poor installation of PV systems was found to be the primary underlying cause of all PV fault scenarios. The main factor is due to lack of fire safety knowledge and negligence behavior of the installers. The consequences of PV fires in the BowTie diagram were investigated from the event tree analysis. Twelve possible outcomes were identified and regrouped to five consequences, that is, respiratory poisons, electrical shock, fall from heights, asset damage, and fire propagation. The evaluation of the consequences of PV fire shows that electrical shock poses a very high risk to the surrounding people, including firefighters. Additional measures are proposed to reduce the impact of electric shock.